Live sustainably now : a low-carbon vision of the good life - Coplan, Karl S. (Columbia University Press, 2020)
"Any realistic response to climate change will require reducing carbon emissions to a sustainable level. Yet even people who already recognize that the climate is the most urgent issue facing the planet struggle to understand their individual responsibilities. Is it even possible to live with a sustainable carbon footprint in modern American society--much less to live well? What are the options for those who would like to make climate awareness part of daily life but don't want to go off the grid or become a hermit? In Live Sustainably Now, Karl Coplan shares his personal journey of attempting to cut back on carbon without giving up the amenities of a suburban middle-class lifestyle. Coplan chronicles the joys and challenges of a year on a carbon budget--kayaking to work, hunting down electric-car charging stations, eating a Mediterranean-style diet, and enjoying plenty of travel on weekends and vacations while avoiding long-distance flights. He explains how to set a personal carbon cap and measure your actual footprint--with his own results detailed in monthly diaries. Presenting the pros and cons of different energy, transportation, and lifestyle options, Live Sustainably Now shows that there does not have to be a trade-off between the ethical obligation to maintain a sustainable carbon footprint and the belief that life should be fulfilling and fun"--